Quaternary ammonium-based biomedical materials: State-of-the-art, toxicological aspects and antimicrobial resistance - Jiao, Yang; Niu, Li-na; Ma, Sai; Li, Jing; Tay, Franklin R.; Chen, Ji-hua (Progress in polymer science, 2017)
Microbial infections affect humans worldwide. Many quaternary ammonium compounds have been synthesized that are not only antibacterial, but also possess antifungal, antiviral and anti-matrix metalloproteinase capabilities. Incorporation of quaternary ammonium moieties into polymers represents one of the most promising strategies for preparation of antimicrobial biomaterials. Various polymerization techniques have been employed to prepare antimicrobial surfaces with quaternary ammonium functionalities; in particular, syntheses involving controlled radical polymerization techniques enable precise control over macromolecular structure, order and functionality. Although recent publications report exciting advances in the biomedical field, some of these technological developments have also been accompanied by potential toxicological and antimicrobial resistance challenges. Recent evidenced-based data on the biomedical applications of antimicrobial quaternary ammonium-containing biomaterials that are based on randomized human clinical trials, the golden standard in contemporary medicinal science, are included in the present review. This should help increase visibility, stimulate debates and spur conversations within a wider scientific community on the implications and plausibility for future developments of quaternary ammonium-based antimicrobial biomaterials.